2020
DOI: 10.21037/tau.2019.08.36
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better testicular sperm extraction: novel sperm sorting technologies for non-motile sperm extracted by microdissection TESE

Abstract: Non-obstructive azoospermia (NOA) is the most severe form of male factor infertility. It is characterized by a lack of spermatogenesis in the seminiferous tubules. Microdissection testicular sperm extraction (microTESE) has significantly improved testicular sperm retrieval rates compared to conventional techniques for NOA. Following testicular biopsy, the sperm is usually non-motile and contained within seminiferous tubules requiring extensive laboratory processing to find individual sperm sufficient for artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Whereas in secondary form, non-surgical treatment may be a viable option, in primary one, surgical sperm retrieval is the main treatment. There are various sperm retrieval techniques with their own advantage and disadvantage (13). (E.g.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas in secondary form, non-surgical treatment may be a viable option, in primary one, surgical sperm retrieval is the main treatment. There are various sperm retrieval techniques with their own advantage and disadvantage (13). (E.g.…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study, testicular spermatozoa could be isolated using this technique in cases of NOA where sperm recovery could not be achieved in previous TESE attempts [ 121 ]. However, alterations in cell viability due to fluorophores and antibodies, the cost of the system, high cell loss, and its time-consuming nature are potential limiting factors for the use of FACS in testicular cell selection for ICSI [ 122 ].…”
Section: Processing and Selection Of Surgically Retrieved Sperm For Icsimentioning
confidence: 99%
“…In addition, sperm from these samples often have different morphologic abnormalities. Applications for purifying testicular sperm are currently being developed (46,48). Hopefully, microfluidics and/or other approaches to automation will have the potential to improve the speed and efficiency of purifying rare sperm in order to rapidly identify high-quality sperm for ICSI, thus replacing the extremely time consuming and labor intensive manual procedure.…”
Section: Essential Pointsmentioning
confidence: 99%
“…The authors reported that this method was potentially useful for treating raw semen and sorting rare sperm samples. Even sperm obtained by testicular sperm extraction can be isolated in this way (48). De Wagenaar et al (62) demonstrated that boar sperm could be separated on a dielectrophoretic field based on a morphologic anomaly, cytoplasmic droplets on the flagellum.…”
Section: Essential Pointsmentioning
confidence: 99%